The Effect of Top Management Support and Occupational Safety and Health (OSH) Programs on Employee Performance with Rewards as a Mediating Variable at PT Argo Manunggal Triasta Tangerang - Nancy Chitrayana; Daniel Widjaja (Journal of Social Research, 2025)
Top management support is crucial to the success of an Occupational Health and Safety (OHS) program. However, the mediating role of rewards in this relationship requires further investigation. While previous studies have established the importance of top management support and OHS programs, the specific role of rewards in mediating these relationships with employee performance remains underexplored. This study aimed to analyze the role of rewards in influencing the relationship between top management support and OHS programs on employee performance at PT. Argo Manunggal Triasta in Tangerang. A quantitative approach was employed with 102 employees of PT. Argo Manunggal Triasta selected through random sampling techniques. Data were collected using a questionnaire with a 5-point Likert scale and analyzed using Structural Equation Modeling (SEM) with Smart PLS 4. The findings indicate that reward provision (variable Z) significantly mediates the influence of top management support (variable X1) on employee performance (variable Y) with a t-statistic of 2.642 > 1.96 and a p-value of 0.008 < 0.05. The OHS program (variable X2) also significantly influences employee performance with a t-statistic of 2.728 > 1.96 and a p-value of 0.006 < 0.05. Companies should maximize top management support by implementing comprehensive reward policies, including bonuses, wage increases, and recognition awards, to motivate employees and enhance OHS program implementation effectiveness.